'Embedded into the core': The discursive construction of 'policy' in higher education learning and teaching documents and its recontextualisation in practices. (September 2020) - Horrod, Sarah
With increasing competition and metrics focusing on teaching quality (e.g. the teaching excellence framework or TEF), there is a spotlight on learning and teaching (L&T) in policies and practices within universities. Bodies at national and institutional levels focus on disseminating policy ideas on L&T which are oriented to government priorities. This article focuses on how policy itself is discursively constructed in selected L&T policy documents and explores the means of the recontextualisation of policy discourses. I discuss the following three findings: (1) the construction of policy as 'embedded within processes and practices', (2) shifts in genre and discursive strategies as policy ideas become short guidelines and (3) the role of 'discursive mechanisms' in forcing engagement with policy ideas. Through an analysis of discursive strategies and recontextualisation, I demonstrate the seeming insecurity around policy compliance and show how constructions of L&T are never value-free.